The malignant transformation of an atypical angiocentric glioma, MYB-altered - Aboubakr, Oumaima; Wefers, Annika K.; Dangouloff-Ros, Volodia; Métais, Alice; Sievers, Philipp; Hasty, Lauren; Saffroy, Raphaël; Pierron, Gaelle; Guillemot, Delphine; Samoyeau, Thomas; Boddaert, Nathalie; Grill, Jacques; et al. (Acta Neuropathologica Communications, 2025)
According to the current World Health Organization classification of central nervous system tumors, the angiocentric glioma (AG) assigned a grade 1, characterized by recurrent MYB fusions. However, it also mentions that increased proliferative activity and other anaplastic features have been reported, but the clinical significance of such findings is unclear as an increased proliferative activity alone does not necessarily alter the benign behavior of AGs. Most cases with “anaplasia” were mainly described before the molecular era. Herein, we report the case of a 3-year-old female with epilepsy symptomatic of a left temporo-parietal tumor. Histopathologically, the initial tumor displayed atypical AG morphology and a proliferation index of 1%, without mitoses, or necrosis. RNA sequencing identified a MYB::QKI fusion. After several tumor recurrences, the last tumor sample showed strong evidence of a histopathological transformation into a high-grade tumor with proliferation and mitotic indexes, necrosis and microvascular proliferation. The recurrent tumor still harbored the same MYB::QKI fusion but acquired an hTERT mutation. DNA-methylation analysis classified the initial tumor as an LGG, MYB/MYBL1-altered (AG, MYB/MYBL1-altered with a calibrated score of 0.58) while the progression clustered with glioblastoma, IDH-wildtype, RTK1 (with a calibrated score of 0.33). The copy number variation both at presentation and at last recurrence (CNV) exhibited a chromosome 6 chromothripsis. The patient died from tumor progression after an overall survival of 89 months. This novel observation raises the question of whether this case represents an aggressive form of MYB/MYBL1-altered LGGs driven by an oncogenic MYB fusion, or if they are actually high-grade gliomas that coincidentally exhibit alterations near the MYB locus. Further reports are needed to confirm the existence of malignant forms of LGG, MYB/MYBL1-altered, potentially correlated with a higher grade.